Implementation of A New Single-Stage Bridgeless Boost Half-Bridge AC/DC Converter with Bidirectional Switch - et. al., Mohamad Affan Mohd Noh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper discussed on the practical implementation of a newly proposed isolated bridgeless single stage AC-DC converter. The step for the practical implementation are discussed in details. These included the design of the printed circuit board, the values of the electronic and magnetic components. In addition, the experiment setup and procedures is also presented. This new circuit topology is implemented and tested at 115 Vac, 50 Hz of input supply and 20 Vdc output voltage with maximum output power of 100 W. It is also tested at input voltage with higher frequency of 500Hz to confirm the elimination of zero crossing of the input current.